Answer:
f(x)⁻¹ = x³ + 2
Step-by-step explanation:
Find the inverse of f(x) = ∛(x - 2).
The first step is to let f(x) = y
y = ∛(x - 2)
Then make x the subject of the formula
y³ = [∛(x - 2)]³
y³ = x - 2
x = y³ + 2
∴ f(x)⁻¹ = y³ + 2
Replacing y with x we have.
f(x)⁻¹ = x³ + 2
Answer:
The mean is 21.62 which is approximately 22
Step-by-step explanation:
mean= 15+20+10+12+20+16+80+18/8=21.62 because
mean= sum of all numbers/numbers mentioned
Answer: 5p - 4
5 times ‘p’ = 5p
4 less than ‘p’ = p - 4
Therefore,
=> 5p - 4
Answer:isisisisisjwjsusjsnss
Step-by-step explanation:
Answer:1. you can compute the slope, m
2. point (0,3) is the y-intercept; b=33
3. y = mx + b, so put the numerical values in for m & b. DON
Step-by-step explanation: